Perinatal care for women with refugee backgrounds from African countries: a qualitative study of intersections with psychological wellbeing - Clemence Due; Moira Walsh; Isadora Aldam; Amelia Winter; Susan Cooper; Josephine Sheriff; Anna Ziersch (BMC, 2022)
Abstract Background Experiences with healthcare services, including perinatal healthcare services, contribute to psychological wellbeing for refugees post-resettlement. To address the paucity of literature examining the relationship between perinatal healthcare and psychological wellbeing in women with refugee backgrounds from African countries this study aimed to: (1) understand the relationship between psychological wellbeing and perinatal care amongst this population, and; (2) identify areas for improved perinatal healthcare services to ensure positive wellbeing outcomes in this population. Methods A total of 39 participants were included in the study. Nineteen women from seven African countries participated in interviews - seven both prior to and after having their babies, two only while pregnant and ten only after their baby had been born. In addition, interviews were conducted with 20 service providers. Interviews were thematically analysed. Results Four key themes were identified, covering continuity of care, cultural safety of care, agency in decision making, and ongoing impacts of perinatal care experiences. Conclusions The results highlighted the need for changes to perinatal healthcare provision at the systems level, including implementing a continuity of care model, and ensuring women's access to individualised, trauma-informed perinatal services which attend to the cultural and psychosocial resettlement needs of this population. These findings informed recommendations for improving perinatal healthcare services and better psychological outcomes - and in turn broader health outcomes - for African-background refugee mothers.